Vegetation of the Verdiana River valley in the northern Apennines, Italy. - Foggi, Bruno; Lastrucci, Lorenzo; Papini, Piera; Vergari, Simone; Gennai, Matilde; Gervasoni, Davide; Viciani, Daniele; Ferretti, Giulio (Lazaroa, 2011)
This work describes the vegetation growing in the valley of the Verdiana Stream in the northern Apennines, near Pistoia, Tuscany. The plant communities are reviewed and analysed using a phytosociological methodology and referenced to the following classes: Montio-Cardaminetea, Asplenietea trichomanis, Galio-Urticetea, Mulgedio-Aconitetea, Nardetea strictae, Rhamno-Prunetea, Salici purpureae-Populetea nigrae and Querco-Fagetea. Several new taxa are described: Asplenio viridis-Cystopteridetum fragilis subass. saxifragetosum cuneifoliae subass. nova and Geranio nodosi-Loniceretum alpigenae ass. nova subass. loniceretosum alpigenae subass. nova and loniceretosum nigrae subass. nova. The study identifies five habitats of significant conservation interest (Directive 92/43 EEC).